Covid-19 Pandemic and the Protection of Older People in International Comparison. Results of Comparative Research from an Ethical Perspective - Forster, Sophia; Frewer, Andreas (Pandemics and Ethics, 2023)
The corona pandemic affects older people in particular: isolation and quarantine in the lockdown, strict visiting regulations in institutions, etc. The protection of the well-being threatened by a Covid-19 infection is to be ensured above all by restricting social contacts. However, regular interpersonal meetings are also a relevant protective factor for physical and mental health. Strict visiting bans are an extreme psychological burden, especially for residents of nursing homes, as the affected people were neither involved in the underlying decision-making process nor were able to resist the resulting regulations. Thus, many residents reacted to the measures taken with incomprehension and rejection. In the following, the course of the pandemic will first be set in a global context from the perspective of Germany (2). Subsequently, central topics will be illuminated which contain particular relevance and ethical brittleness in the question of the protection of older groups of people (2.1–2.4). This will be followed by a detailed comparison of the situation in nursing and old people’s homes in different countries in order to gain an orientation about the local situation there (3.1–3.2). The results of the analysis also reveal potential sources of error in international comparisons. Finally, a comprehensive principles reflection rounds off the contribution (4) and central final considerations give an outlook on the still dynamic course of events (5).
CRIS-Team Scopus Importer:2024-06-28

‘Prioritized Distribution of Equal Shares’—An Ethical and Practicable Allocation Framework for COVID-19 Vaccines - Heuberger, Lina Corinna; Forster, Sophia; Frewer, Andreas (Philosophies, 2023)
In the context of the global COVID-19 pandemic, the fast and equitable distribution of effective vaccines worldwide is one of the challenges faced by international institutions in charge, as global equity in vaccine supply has not yet been achieved. Our paper explains the current state of ethical research on equity in global COVID-19 vaccine allocation, focusing on the COVAX Facility established by the WHO, acting as the global vaccine distributor. The article presents a detailed analysis of the first year of COVAX allocation in 2021 identifying problematic aspects of its allocation framework regarding the implementation of COVAX’s fundamental allocation principles. We argue that the COVAX Facility has developed a proper concept to deal with global vaccine allocation—but to address uncovered defaults, we introduce the ‘Prioritized Distribution of Equal Shares’ model—a both ethical and practically feasible alternative allocation framework to protect the value of human lives in both high- and low-income countries through fair and fast global vaccine distribution in health emergencies. Nonetheless, we argue that the COVAX Facility remains the main organization to provide equitable access to vaccines. Yet, the global community has to consider further aspects such as patent protection, vaccine production and the lack of power of global structures to address the inequities that have arisen. Since new wars and further crises have arisen, a shift in public global attention endangers the processing of COVID-19-related issues. That is why now more than ever extensive efforts to achieve vaccine equity are needed.
CRIS-Team Scopus Importer:2023-05-05
Keywords: allocation; COVAX; COVID-19; distributional justice; global health ethics; human rights; vaccine